Women and Hijab in the Arms of Media, Popular Culture, and Globalization - Chaniago, Rizky Hafiz; Yusuf, Sarina; Mubin, Nur Nadia; Hassan, Mohd Sufiean (I-Pop: International Journal of Indonesian Popular Culture and Communication, 2022)
In essence, Islam was revealed to elevate the dignity of every woman who was previously oppressed by the tradition of the Jahiliya community before the 6th century AD. In the context of humanities, Islam does not justify discrimination between men and women. One form of anti-discrimination against women is the recommendation to wear the hijab (the use of a veil). The presence of the hijab is intended to safeguard the respect of women but raises another issue, namely the right to freedom. However, the purpose of hijab for Muslim women has almost always been problematic due to their position in two circumstances: benefited or harmed. The hijab is often understood as an attempt to suppress women's lives. The role of hijab in the era of globalization today is still relatively small; the powerlessness of women in the industrial world is influenced by the social construction that tends to represent women who are only suitable for the domestic sector. The influences of the mass media on the image of women who wear the hijab also cover the voices of the group so that public perceptions generally believe that this condition is proper. As a conceptual study, this article examines the position of the hijab in the current era of globalization and its relationship to media and popular culture. This study uses a document analysis method. The data collected are excerpts from document manuscripts, research journals, and scientific articles.